Differential expression of urokinase-type Plasminogen Activator (uPA), its Receptor (uPA-R), and Inhibitor type-2 (PAI-2) during differentiation of keratinocytes in an organotypic coculture system - Schäfer, Birgit; Stark, Hans-Jürgen; Fusenig, Norbert; Todd, Robert F.; Kramer, Michael D. (Experimental cell research, 1995)
Cultured keratinocytes resemble migrating keratinocytes under conditions of reepithelialization during wound healing. Such keratinocytes express urokinase-type plasminogen activator (uPA) and its specific receptor (uPA receptor). Receptor-bound uPA activates plasminogen, thus providing plasmin for pericellular proteolysis. uPA is regulated by the plasminogen activator inhibitors PAI-1 and PAI-2. As indicated by immunohistology, neither uPA nor uPA receptor is expressed in normal epidermis. Thus, the down-regulation of uPA and uPA-receptor expression in keratinocytes appears to be an important event in epidermal healing and restoration of a normal epidermal tissue architecture. We have addressed this matter by using a culture and differentiation system for keratinocytes in vitro. Keratinocytes were grown in organotypic cocultures for 4, 7, and 14 days. Frozen sections were analyzed with indirect immunofluorescence staining and overlay zymography, the latter detecting activity of plasminogen activators. While tPA and PAI-I stainings were consistently negative over the entire observation period, uPA and uPA receptor were expressed by basal keratinocytes at Days 4 and 7, but not at Day 14. Accordingly, overlay zymography revealed uPA activity at Days 4 and 7. PAI-2 was found throughout the entire observation period, but with varying distribution: at Days 4 and 7 all suprabasal keratinocytes stained positive for PAI-2. At Day 14, PAI-2-specific stainings were confined to the uppermost cells of the stratum spinosum. Our data demonstrate that uPA and uPA receptor, which are up-regulated in cultured keratinocytes, are down-regulated upon restoration of an epidermis-like structure. The distribution of PAI-2 varied over the observation period and at Day 14 resembled the distribution of PAI-2 in normal epidermis. Taken together, keratinocytes in organotypic coculture behave like keratinocytes in healing wounds in vivo with respect to the expression of the plasminogen activator system.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 27.02.2025